Can Visually Impaired Use Gestures to Interact with Computers? A Cognitive Load Perspective - Modanwal G.; Rai S.B.; Jaiswal A.; Singh T.; Sarawadekar K. (My University, 2025)
Production of gestures does not require vision. Everyone - even those who are blind since birth - produces hand gestures while interacting with others. In our previous study, a gesture-based technique called Dactylology has been developed for the visually impaired to help them interact with computers. Cognitive load is an important indicator and a critical research issue while designing and adopting such new techniques. Hence, a study was conducted to compare the performance on a task between two computer input techniques (i.e., Dactylology and Braille) under varying levels of cognitive load (low, medium, and high), introduced by manipulating the task complexity. For the purpose of the study, 14 visually impaired participants were trained on Dactylology and Braille techniques to interact with the computer. The task performance was measured through the response time (RT) and false responses (FR). The results confirm that the participants had significantly lower RT and committed fewer FR in the Dactylology technique than the Braille under all cognitive load conditions. Altogether, these results render sufficient support to consider gesture-based Dactylology as a potential technique for the visually impaired to interact with the computer. © 2013 IEEE.